Financial Literacy as a Mediator Between Digital Engagement and Gen Z Students' Financial Preparedness - I Made Rama Sugiartha; Muhammad Ahyar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of Digital Financial Engagement (DFE) on Financial Preparedness (FP) among Generation Z college students in Indonesia, with Financial Literacy (FL) serving as a mediating variable. Employing a quantitative approach, data were collected from 231 Generation Z students who actively use digital financial services, and analyzed using Structural Equation Modeling (SEM) with AMOS. The findings reveal that DFE has a positive and significant effect on both FL (β = 0.218; p < 0.001) and FP (β = 0.144; p < 0.001). Furthermore, FL exerts a strong positive influence on FP (β = 0.534; p < 0.001). The mediation test using the Sobel method confirms that FL partially mediates the relationship between DFE and FP (Z = 3.871; p < 0.001), suggesting the presence of both direct and indirect effects. Theoretically, this study enriches the literature on financial behavior by highlighting the role of digital financial practices in fostering preparedness for future financial needs. Practically, the results emphasize the importance of integrating financial literacy education into higher education curricula and promoting responsible engagement with digital financial platforms to enhance young adults’ financial readiness in an increasingly digitalized economy.